Comparison of planar quasi-Yagi antenna with different substrate for X-band radar applications / Shiman Saiman - Saiman, Shiman (2015)
This paper presents a comparison of planar quasi-Yagi antenna with different substrate for X-band radar applications. The antenna were fabricated with substrates of Rogers RT6010 and FR-4. The X-band radar applications were in frequency range of 8 GHz to 12 GHz. The main purpose of this paper is to determine which antenna has better performance. The software used is Computer Simulation Technology 2011(CST). The criteria that needed to analyze are the S-parameter, VSWR, return loss, and the radiation pattern. All parameter of the antenna can be measure by using Vector Network Analyzer (VNA).